Academic Supervision Model Based On Video Conference For Teacher Of Smk Negeri In Wonosari Sub-District, Gunungkidul Regency - Rustianto, Arif; Rusdarti, Rusdarti; Prihatin, Titi (Educational Management, 2018)
Academic supervision is a supervisory assistance service to teachers both individually and in groups. The number of supervisors who are not proportional to the number of teachers as well as limited time and space are the obstacles that exist in the implementation of academic supervision. The objectives of this research are (1) to know and analyse the factual model of academic supervision; (2) to develop hypothetical model of video conference-based academic supervision; and (3) to know and analyse the feasibility of the use of video conference-based academic supervision model.The method used in this research is RnD (Research and Development). The subject of this research is supervisors and teachers of SMK (Sekolah Menengah Kejuruan- Vocational School) in Wonosari sub-district, Gunungkidul regency. The data are analysed quantitatively and qualitatively. The final model of video conference-based academic supervision is obtained by describing the factual model of academic supervision, developing conceptual models, validating conceptual model, testing the hypothetical models, and formulating a final model of video conference-based academic supervision.The result shows that the factual model of academic supervision is less optimum because it is constrained by the number of teachers, limited time and quite wide location. At the development stage, it produces hypothetical models that have been validated by experts and practitioners. Then, the final model with feasibility test for supervisor and teacher resulted in very good category model. The conclusion of this research is that the model of academic supervision based on video conference is very feasible to be implemented.This research suggests that supervisors could immediately adopt a conference video-based academic supervision model to solve the current problems; the number of teachers to be guided, the limited time and the wide location.